(untitled) (Journal of Health, Technology and Science (JHTS), 2025)
Work fatigue is one of the crucial issues in the mining industry that has a significant impact on safety, health, and work productivity. This study aims to comprehensively examine the factors causing work-related fatigue, its impact on workers, and the measurement strategies used in various mining work contexts. This is done through a systematic literature review of national and international publications, particularly from the past five years (2019-2025). This study employs the Systematic Literature Review (SLR) method, utilising academic databases such as Scopus and Google Scholar, resulting in the synthesis of 10 articles. The results of the Systematic Literature Review (SLR) indicate that work-related fatigue is influenced by various factors such as age, tenure, shift systems, physical and mental workloads, and extreme work environment conditions. Additionally, psychosocial factors such as work-related stress, work-life balance, and production target pressures were also identified as significant contributors to work-related fatigue. The strategies for measuring fatigue in this study varied, ranging from subjective methods such as the MFI-20 questionnaire, SCL-90, PHQ-9, and GAD-7, to objective approaches such as wearable sensors, operational data from heavy machinery, and the application of machine learning for real- time fatigue prediction in underground mines. The findings of this review emphasise the importance of a multidimensional approach in assessing work-related fatigue and the need for integrated interventions that include shift work management, workload control, technology-based operator condition monitoring, and mental health support programmes.